2021
DOI: 10.3390/jcm10163644
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Withania somnifera (Ashwagandha) Extract—A Randomized, Double-Blind, Placebo Controlled Trial with an Open Label Extension on Healthy Participants

Abstract: The immunomodulatory effect of Withania somnifera (WS) extract was tested in healthy adults. In this randomized placebo-controlled double-blinded study, subjects were allocated either 60 mg WS extract or placebo. It consists of a blinded 30-day period and an open-label extension study of another 30 days with crossover of only placebo to test. After the 30-day blinded study period, the WS test group reported significant increase (p < 0.05) in Ig’s (IgA, IgM, IgG, IgG2, IgG3 and IgG4), Cytokines (IFN-γ, IL4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…While recent studies on safety show no effect on elevation levels of thyroid hormone, 16 the potential to modulate thyroid hormone level is cause for ashwagandha to be contraindicated for individuals taking thyroid medications. Furthermore, ashwagandha has been seen in recent studies to increase immunoglobulin levels and cytokine activity 49 and thus should be avoided for individuals with autoimmune disorders. Due to its effects on the immune response, individuals who may be undergoing surgical procedures should notify their surgeon of the use of this herb and follow physician recommended discontinuation guidelines prior to any surgical procedure.…”
Section: Strategies For Safe Usementioning
confidence: 99%
“…While recent studies on safety show no effect on elevation levels of thyroid hormone, 16 the potential to modulate thyroid hormone level is cause for ashwagandha to be contraindicated for individuals taking thyroid medications. Furthermore, ashwagandha has been seen in recent studies to increase immunoglobulin levels and cytokine activity 49 and thus should be avoided for individuals with autoimmune disorders. Due to its effects on the immune response, individuals who may be undergoing surgical procedures should notify their surgeon of the use of this herb and follow physician recommended discontinuation guidelines prior to any surgical procedure.…”
Section: Strategies For Safe Usementioning
confidence: 99%
“…The results of this study demonstrate that the Withania somnifera of defined chemical signature with its immune-stimulatory activities is a valuable addition to immunity-boosting herbal supplements. These effects span both innate and adaptive immunity, which may partially explain its traditional use as a Rasayana or rejuvenating herb with anti-stress properties [16] .  Extracts from Withania somnifera (L.), known as WST and WS2, were examined for their immunomodulatory properties in mice for immunological inflammation: active paw anaphylaxis and delayed-type (DTH).…”
Section: Acting At the Level Of Srotasmentioning
confidence: 99%
“…Some phyto-nutraceutical compound showed positive results against osteoporosis. For instance, in 2021, Tharakan and co-workers reported a positive immunomodulatory effect of Withania somnifera extract during preclinical studies which significantly increased the production of cytokines IFN-γ, IL-4, and CD45+, CD3+, CD4+, CD8+, and CD19+ NK cells ( 163 ). Moreover, Zaffar Azam et al recently reported that guggul extract, arjuna, coriolus versicolor, and Punica granatum showed a promising immunomodulatory effect for the management of bone health ( 164 ).…”
Section: Immunomodulatory Nutraceuticals Toward Management Of Non-com...mentioning
confidence: 99%